2018
DOI: 10.12659/msm.906437
|View full text |Cite
|
Sign up to set email alerts
|

A Voxel-Based Magnetic Resonance Imaging Morphometric Study of Cerebral and Cerebellar Gray Matter in Patients Under 65 Years with Essential Tremor

Abstract: BackgroundThe aim of this study was to compare the morphological changes in cerebral and cerebellar gray matter in patients with essential tremor under 60-years-of-age, with age-matched and gender-matched normal healthy volunteer control subjects, using functional magnetic resonance imaging (fMRI) and voxel-based morphometry (VBM) analysis.Material/MethodsA retrospective, controlled, comparative clinical study included 17 patients with essential tremor, <60 years-of-age, and 17 age-matched and gender-matched h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 31 publications
1
22
0
1
Order By: Relevance
“…55 showed different findings, with compensatory increase of the gray matter in the cerebellum and other brain areas, 18,19 rather than atrophy showed by older studies. 55 showed different findings, with compensatory increase of the gray matter in the cerebellum and other brain areas, 18,19 rather than atrophy showed by older studies.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…55 showed different findings, with compensatory increase of the gray matter in the cerebellum and other brain areas, 18,19 rather than atrophy showed by older studies. 55 showed different findings, with compensatory increase of the gray matter in the cerebellum and other brain areas, 18,19 rather than atrophy showed by older studies.…”
Section: Discussionmentioning
confidence: 81%
“…It could be accepted that studies, where no cerebellar signs or other neurological deficits mentioned, have used only essential tremor patients, but whether their findings could be reliable is still questionable while they had not used the new diagnostic criteria and there is a strong risk of patients with different types of tremor may have been included. Most recent studies using the new classification for tremor and the new diagnostic criteria for essential tremor showed different findings, with compensatory increase of the gray matter in the cerebellum and other brain areas, 18,19 rather than atrophy showed by older studies. [10][11][12][13][14][15] Further studies which will consider the new classification of tremor and will rigorously apply the new diagnostic criteria for essential tremor and which will categorize patient based on both clinical phenotypes and the etiology needed in order to clarify the microscopic and macroscopic changes in essential tremor.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, Bhalsing et al detected GM volume reduction covering the anterior and posterior lobules of the cerebellum bilaterally in ET associated with cognitive impairment 18 . On the other hand, several studies did not show any differences in GM cerebral and cerebellar volumes between ET patients and HC 13,[19][20][21][22] , whereas others reported increased GM volumes of the bilateral cerebellum 23,24 and right occipital fusiform gyrus 24 in ET patients. Discrepancies among studies might be attributable to patient selection reflecting, among others, less stringent diagnostic criteria for ET in the past, as well as to different MRI field strengths and heterogeneous anatomical sequences acquired in the populations 11 .…”
Section: Discussionmentioning
confidence: 86%
“…Neuroimaging studies also demonstrated structural changes in grey matter regions as frontal, temporal and occipital cortex [22,[30][31][32][33], insula, precuneus [22,31], basal ganglia, red nucleus, substantia nigra and thalamus [34]. Neurodegenerative nature of the disease and a number of accompanying non-motor symptoms suggest that this neurodegeneration may also spread to white matter.…”
Section: Introductionmentioning
confidence: 97%
“…As a result, reduced purkinje cell inhibitory output and impaired fiber connections between cerebellar cortex and dentate nucleus were observed [20,21]. Functional and structural neuroimaging studies identified the involvement of cerebellar pathways [16,22,[23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%